Genetic Polymorphism Effect on Warfarin–Rifampin Interaction: A Case Report and Review of Literature - Muhammad Salem (8979428) (2021)
Warfarin–rifampin interaction has been reported since the 1970s. Due to rifampin’s strong induction of CYP2C9, most cases could not attain the target international normalized ratio (INR) despite warfarin dose escalation. Genetic polymorphisms determine up to 50% of warfarin dose variability. A 38-year-old woman was started on warfarin and rifampin for cerebral venous sinus thrombosis and pulmonary tuberculosis. Over six weeks, the daily warfarin dose was increased from 3 to 10 mg to attain three consecutive in-clinic therapeutic INRs. She completed three complications-free months of warfarin treatment with time in therapeutic range (TTR) of 46%. We performed retrospective genetic testing to determine the patient’s CYP2C9, CYP4F2, and VKORC1 genotypes and whether they had affected the interaction outcome. The analysis revealed that the subject carries CYP2C9*3*3 and VKORC1-1639 (GA) mutations, classifying her as a slow metabolizer and, hence, highly warfarin-sensitive. This was reflected on how the case responded to a relatively lower dose than previously reported cases that did not achieve the target on warfarin daily doses up to 35 mg. This is the first report addressing the genotype effect on this interaction. Patients with genetic variants requiring low warfarin doses are more likely to respond at a feasible dose while on rifampin. Future studies to evaluate warfarin–rifampin-gene interaction are warranted. Other Information Published in: Pharmacogenomics and Personalized Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.2147/pgpm.s288918